Single-isocenter volumetric modulated arc therapy vs. cyberknife M6 for the stereotactic radiosurgery of multiple brain metastases - El-Shafie, Rami; Schmitt, Daniela; Kronsteiner, Dorothea; Uzun-Lang, Kristin; König, Laila; Höne, Simon; Forster, Tobias; Nettelbladt, Bastian von; Adeberg, Sebastian; Debus, Jürgen; Rieken, Stefan; Bernhardt, Denise (Frontiers in oncology, 2020)
Introduction: Stereotactic radiosurgery (SRS) is becoming more frequently used for patients with multiple brain metastases (BM). Single-isocenter volumetric modulated arc therapy (SI-VMAT) is an emerging alternative to dedicated systems such as CyberKnife (CK). We present a dosimetric comparison between CyberKnife M6 and SI-VMAT, planned at RayStation V8B, for the simultaneous SRS of five or more BM. Patients and methods: 20 treatment plans of CK-based single-session SRS to ≥5 brain metastases were re-planned using SI-VMAT for delivery at an Elekta VersaHD linear accelerator. Prescription dose was 20 or 18 Gy, conformally enclosing at least 98% of the total Planning Target Volume (PTV), with PTV margin-width adapted to the respective SRS technique. Comparatively analyzed quality metrics included dose distribution to the healthy brain (HB), including different isodose volumes, conformity and gradient indices. Estimated treatment time was also compared. Results: Median HB isodose volumes for 3, 5, 8, 10 and 12 Gy were consistently smaller for CK-SRS, compared to SI-VMAT (p<0.001). Dose falloff outside the target volume, as expressed by the gradient indices GI_high and GI_low, was consistently steeper for CK-SRS, compared to SI-VMAT (p<0.001). CK-SRS achieved a median GI_high of 3.1 [IQR 2.9 - 1.3] vs. 5.0 [IQR 4.3 - 5.5] for SI-VMAT (p<0.001). For GI_low, the results were 3.0 [IQR 2.9 - 3.1] for CK-SRS vs. 5.6 [IQR4.3 - 5.5] for SI-VMAT (p<0.001). The median conformity index (CI) was 1.2 [IQR 1.1 - 1.2] for CK-SRS vs. 1.5 [IQR 1.4 - 1.7) for SI-VMAT (p<0.001). Estimated treatment time was shorter for SI-VMAT, yielding a median of 13.7 min [IQR13.5 - 14.0], compared to 130 min [IQR 114.5 - 154.5] for CK-SRS (p<0.001). Conclusion: SI-VMAT offers enhanced treatment efficiency in cases with multiple BM, as compared to CyberKnife, but requires compromise regarding conformity and integral dose to the healthy brain. Additionally, delivery at a conventional linac may require larger safetya larger PTV margin to account for delivery and setup errorss. Further evaluations are warranted to determine whether the detected dosimetric differences are clinically relevant. SI-VMAT could be a reasonable alternative to a dedicated radiosurgery system for selected patients with multiple BM.